1998
DOI: 10.1063/1.120957
|View full text |Cite
|
Sign up to set email alerts
|

n -type electrical conduction in transparent thin films of delafossite-type AgInO2

Abstract: Thin films of AgInO2 were prepared to find a transparent and n-type conducting oxide with a delafossite structure. This is a candidate material for fabricating a pn junction with the recently found p type conducting and transparent CuAlO2 delafossite. Nondoped and 5% Sn-doped thin films were deposited on a silica glass substrate by radio-frequency sputtering. The crystalline phase in the films was identified to be the delafossite structure by x-ray diffraction and chemical composition was confirmed to be an Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 6 publications
5
42
0
Order By: Relevance
“…In this regard, it is also worthwhile to mention that the M III O 2 layers of this structure is also important for designing n-TCOs, specially for the cations like Ga þ3 , In þ3 in the M III sites with s 0 configuration [70]. Following the above argument, a delafossite AgInO 2 thin film with n-type semiconductivity has already been demonstrated [36].…”
Section: Criteria To Choose P-tcomentioning
confidence: 93%
“…In this regard, it is also worthwhile to mention that the M III O 2 layers of this structure is also important for designing n-TCOs, specially for the cations like Ga þ3 , In þ3 in the M III sites with s 0 configuration [70]. Following the above argument, a delafossite AgInO 2 thin film with n-type semiconductivity has already been demonstrated [36].…”
Section: Criteria To Choose P-tcomentioning
confidence: 93%
“…Corresponding Ag-based delafossite materials are difficult to synthesize by simple solid-state reaction [119,126]. The first report of Ag-based delafossite thin film was AgInO 2 , which is n-type in nature [127]. Later, Nagrajan et al [128] reported that Mg-doped AgInO 2 powder (AgIn 1−x Mg x O 2 , x = 0.1), when treated with fluorine or highpressure oxygen, p-type nature was observed with conductivity as low as 10 −6 S cm −1 .…”
Section: P-tco With Delafossite Structurementioning
confidence: 99%
“…[15,[33][34][35][36][37][38][39][40]. These have interesting electronic/optoelectronic applications but have yet to break into the TSO industry for high volume production because of their costly and complex fabrication processes.…”
Section: Introductionmentioning
confidence: 99%